If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(24 + 8y) = -4 (24 * -4 + 8y * -4) = -4 (-96 + -32y) = -4 Solving -96 + -32y = -4 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '96' to each side of the equation. -96 + 96 + -32y = -4 + 96 Combine like terms: -96 + 96 = 0 0 + -32y = -4 + 96 -32y = -4 + 96 Combine like terms: -4 + 96 = 92 -32y = 92 Divide each side by '-32'. y = -2.875 Simplifying y = -2.875
| (2x^2)+7x+12= | | X+14=1000 | | 0=6x+14y+14 | | 11(2q-8)=-4(7-3q)0 | | 2/3x-9=-4 | | 5/7=5/6•r | | cos(6x)=1-2sin^2(3x) | | 4x+6y=84 | | x-(x*0.1)=90 | | R•5/6=5/7 | | 11c-2c=144 | | V-5=3/4 | | 10x+63=-2.0x+15 | | v/5=0.1 | | 25-10d^2=0 | | X^2-100/x^2 | | c=9m+4 | | 1/2w−12=18 | | -3k+-5=1 | | c=9+4 | | z+3.2=7.1 | | 9=1+2c | | y^2*X^3=128 | | (5c-2)(3c+4)= | | A-5.6=2.8 | | 13x-38=7x+4 | | Y/2=1.6 | | 2y=2-3x | | -5-6-3+b=-7b-5 | | 1/2(2h−4)=20 | | 6-3x-2-3=93 | | 4b^3+13b^2=0 |